Survey of Knowledge Flow in Knowledge based Organization of Science and Technology Park of the University of Tehran and Presentation of a Conceptual Mode - Mohammad Hassanzadeh; Mahtab Teymori Tabieh (بازیابی دانش و نظام‌های معنایی, 2015)
Knowledge has been a competitive weapon in New World.  Being aware of knowledge process in organizations, especially research-oriented ones, and tactfully managing it, will increase their ability and improve their outputs, While unawareness and its improper management could lead to a waste of time, money and energy. Co-operation and relation between organizations will be stable and progressive by knowledge flow, although it is a subconscious issue. Whatever, clarifying and distinguishing this flow in the organization will be a competitive advantage issue. Due to this, the organization will achieve knowledge and use this faster than other organizations. Purpose: The main aim of this paper is survey a of knowledge flow in Knowledge-Based companies of Science and Technology Park of Tehran University and presenting a conceptual model. This kind of studies can enable preliminary programs to result success in an organization. Methodology: Approach of this paper is qualitative and in data gathering researcher used a Questionnaire including 57 questions; and for data analyses used SPSS and One-Sample T Test. Conclusion: Findings show that knowledge flow in knowledge based companies in the knowledge gateways, knowledge flow mechanisms, staff awareness, organizational culture, organizational structure, knowledge flow programming and knowledge sharing factors have not been in a good state. The ideal conceptual model of knowledge flow present after literature review and analyses of X-ones.